The Research of DV-HOP Positioning Algorithm Based on RSSI Calibration - Jie Cao; Mu Chen (Institute of Advanced Engineering and Science, 2014)
Because of the DV-HOP algorithm in wireless sensor network (WSN), the first jump range error, which affect the positioning error of the whole node network problems. This paper puts forward an improved algorithm is proposed. The algorithm is mainly using the RSSI ranging technology, in the process of DV-HOP first jump range through correction of RSSI ranging technology, to reduce the distance measuring error, in order to improve positioning accuracy. The simulation results show that compared with traditional DV - HOP algorithm. The improved algorithm can without additional hardware and computation under the premise of improving positioning accuracy.